Base station sleep mechanism based on power consumption and energy cost balance - Dongsheng HAN; Bing ZHENG; Zhixiong CHEN (Dianxin kexue)
Deploying dense network in 5G system increases the number of nodes,which leads to a sharp increase in power consumption of wireless communication system,aggravates the economic burden of mobile network operator and exacerbates the emission of CO2.Therefore,considering the number of candidate base station (BS) group and the relative position of the BS supplied by new energy,a comprehensive power consumption model in wireless communication system was investigated in terms of the power consumption and economical level.A base station sleep algorithm based on power consumption and energy cost balance was proposed to achieve a tradeoff between them,which selected candidate groups according to the corresponding power consumption and then determined the active group by choosing the cheapest ones.Simulation results show that the proposed algorithm can significantly reduce energy cost of communication bases system although it leads to a negligible increase in power consumption.